Biomechanical Effects of a New Macrogeometry Design of Dental Implants: An In Vitro Experimental Analysis - Sergio Alexandre Gehrke; Leticia Pérez-Díaz; Patricia Mazón; Piedad N. De Aza (Journal of Functional Biomaterials, 2019)
The purpose of the present study was to measure and compare the insertion torque, removal torque, and the implant stability quotient by resonance frequency analysis in different polyurethane block densities of two implant macrogeometries. Four different polyurethane synthetic bone blocks were used with three cortical thickness: Bone 1 with a cortical thickness of 1 mm, Bone 2 with a cortical thickness of 2 mm, Bone 3 with a cortical thickness of 3 mm, and Bone 4, which was totally cortical. Four groups were created in accordance with the implant macrogeometry (n = 10 per group) and surface treatment: G1—regular implant design without surface treatment; G2—regular implant design with surface treatment; G3—new implant design without surface treatment; G4—new implant design with surface treatment. All implants used were 4 mm in diameter and 10 mm in length and manufactured in commercially pure titanium (grade IV) by Implacil De Bortoli (São Paulo, Brazil). The implants were installed using a computed torque machine, and following installation of the implant, the stability quotient (implant stability quotient, ISQ) values were measured in two directions using Osstell devices. The data were analyzed by considering the 5% level of significance. All implant groups showed similar mean ISQ values without statistical differences (p > 0.05), for the same synthetic bone block: for Bone 1, the value was 57.7 ± 3.0; for Bone 2, it was 58.6 ± 2.2; for Bone 3, it was 60.6 ± 2.3; and for Bone 4, it was 68.5 ± 2.8. However, the insertion torque showed similar higher values for the regular macrogeometry (G1 and G2 groups) in comparison with the new implant macrogeometry (G3 and G4 groups). The analysis of the results found that primary stability does not simply depend on the insertion torque but also on the bone quality. In comparison with the regular implant macrogeometry, the new implant macrogeometry decreased the insertion torque without affecting the implant stability quotient values.